PERKEMBANGAN SMA NEGERI 1 MORO DI KECAMATAN MORO, KABUPATEN KARIMUN (1993-2014) - Rachmawati '; Ridwan Melay Ridwan Melay; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abtract: Schools are the means which are designed to implement education. The more advanced societies increasingly important role of school in preparing young people before entering into the process of community development. In connection with that then in the year two thousand and more schools are built by the Government and society, one with SMA Negeri 1 which is located in the district of Moro Karimun. Seeing this reality, the benefits of SMA Negeri 1 Moro is strongly felt by the community. This is evident from the number of people who put their children in the high school.The purpose of this study was (1) To determine the background establishment of SMA Negeri 1 Moro. (2) To determine the development of SMA Negeri 1 Moro Moro subdistrict Karimun. (3) To determine the factors driving and inhibiting in developing SMA Moro Moro in District of Karimun district. This research method is descriptive. Where the research is the District Moro, Karimun. When the study for 4 months, starting from the research proposal seminar continued with a thesis to graduate exam. Data collection techniques in this study include three techniques yaituteknik observation, Technical Interview (Interview) and Technical Documentation. Data collection and analysis techniques are qualitative. The results of this study are originated from the pioneering Moro Education Foundation which aims to nurture, teach and educate students / i District of Moro. Establishment of SMA Negeri 1 Moro in 1993 with the waqf land / vacant land donated by Alm. H. Wahab voluntarily with the intention of improving education in the District of Moro. In 1994 it became a public school high school. The ideals of its founders affirmed by the decree of the Ministry of Education and Culture of the Republic of Indonesia on October 5, 1994 No. 0260 / O / 1994 on the opening and the nationalization of the school.Keywords: Development Of SMA Negeri 1 Moro In District Karimun